O nekaterih poznolatenskili naseljih na severnem Hrvaškem in njihovem odnosu do središč zgodnje romanizacije - Majnarič-Pandžič, Nives (Arheološki vestnik, 1996)
A large number of late La Tene settlements have been investigated in northern Croatia after World War II. Some have been systematically excavated, but more commonly (and with considerably greater surface areas) the sites have been subject to rescue excavation. The results of such research have neither been studied nor published to date, other than in the form of brief reports. Some of these late La Tene settlements (Orolik, Privlaka, Stari Mikanovei, and Osijek) are currently being analyzed, which should result in a synthetic work in the form of a monograph. This article presents a summary of the basic information about the investigated sites, and discusses various problems resulting from these researches, particularly in terms of the specific manner of fortification of these settlements, as well as the first results of the classification of pottery types.